Precipitous change of the irreversible strain limit with heat-treatment temperature in Nb(3)Sn wires made by the restacked-rod process - Cheggour, Najib (Sci Rep, 2018)
The intrinsic irreversible strain limit ε(irr,0) of Nb(3)Sn superconducting wires, made by the restacked-rod process and doped with either Ti or Ta, undergoes a precipitous change as a function of temperature θ of the final heat-treatment for forming the A15 phase. Nb(3)Sn transitions from a highly brittle state where it cracks as soon as it is subjected to an axial tensile strain of any measurable amount, to a state more resilient to tensile strain as high as 0.4%. The remarkable abruptness of this transition (as most of it occurs over a range of only 10 °C) could pose real challenges for the heat-treatment of large magnets, such as those fabricated for the high-luminosity upgrade of the Large Hadron Collider (LHC). We named this behavior the strain irreversibility cliff (SIC) to caution magnet developers. The approach to fulfilling application requirements just in terms of the conductor’s residual resistivity ratio RRR and critical-current density J(c) is incomplete. Along with RRR and J(c) wire specifications, and sub-element size requirements that reduce wire magnetization and instabilities effects, SIC imposes additional constraints on the choice of heat-treatment conditions to ensure mechanical integrity of the conductor.